Are teachers biased when nominating students for gifted services? Evidence from Kazakhstan - Hernández-Torrano, Daniel; Tursunbayeva, Xeniya (High Ability Studies, 2015)
The purpose of this experimental, vignette study was to analyze whether certain demographic characteristics of students (i.e. gender, ethnicity, and socioeconomic status) influence secondary education teachers in referring students for gifted services in Kazakhstan. A sample of 132 teachers were randomly assigned to one of eight profiles describing a typical gifted student with particular demographics and requested to indicate how strongly they believed the student should or should not be recommended for gifted services. Results evidenced that gender, ethnicity, and SES did not influence the Kazakhstani teachers’ referrals. The implications of teacher nominations in students’ identification for gifted programs and the discussion on the role of gifted education as perceived by school teachers in Kazakhstan and elsewhere are provided.
Keywords: ethnicity; gender; gifted; Kazakhstan; socioeconomic status; teacher referral